Recidivism Among Young Parolees: a Study of Inmates Released from Prison in 22 States, 1978 ([Verlag nicht ermittelbar], 1988)
This study examines the criminal activities of a group of young offenders after their release from prison to parole supervision. Previous studies have examined recidivism using arrests as the principal measure, whereas this study examines a variety of factors, including length of incarceration, age, sex, race, prior arrest record, prosecutions, length of time between parole and rearrest, parolees not prosecuted for new offenses but having their parole revoked, rearrests in states other than the paroling states, and the nature and location of rearrest charges. Parolees in the 22 states covered in this study account for 50 percent of all state prisoners paroled in the United States in 1978.